P156 PSYCHOLOGICAL STRESS INDUCES ALTERATIONS IN BEHAVIOR AND THE MUCOSAL IMMUNE SYSTEM IN A SPONTANEOUS MOUSE MODEL OF ILEITIS. (7th February 2019) - Gomez-Nguyen, Adrian; Buttò, Ludovica F; Basson, Abigail R; Pizarro, Theresa; Cominelli, Fabio
Abstract: Background: Patients with Crohn's disease (CD) suffer from abnormally high rates of depression and anxiety. Depression among patients with CD are higher than other debilitating chronic medical conditions, such as cancer. Behavioral co-morbidities are associated with increased rates of flares, more severe disease course, and increased rate of corticosteroid prescription. Psychological stress, even among CD patients in remission, is recognized as a risk factor for flare-ups. Despite the well-established relationship between stress and symptom relapse, a rigorous mechanistic explanation remains elusive. Here we demonstrate alterations in the behavioral profile and the mucosal immune system in the SAMP1/YitFc (SAMP1) mouse, a spontaneous model of CD-like ileitis, following exposure to acute and chronic psychological stress. Methods: SAMP1 littermates were sex matched and divided into two groups (n=8). The first group was subjected to restraint stress (RS) for seven days. Mice were restrained for 180 minutes per day in a 50mL conical tube with air holes drilled for adequate ventilation. Stool samples were collected each day. Subsequently, each group was subjected to behavioral testing to determine anxiety-like behavior (open field and elevated plus maze), depressive-like behavior (tail suspension), motor deficits (line crossings and rota-rod), and cognitive deficits (Y-maze). Immediately after, mice were sacrificed and tissue samples were collected for immunological analysis. Results: Mice subjected to RS displayed increased immobility time during tail suspension indicating a depressive-like phenotype (p < 0.05). All other behavioral characteristics remained unchanged compared to control. Interestingly, FACS analysis revealed that RS mice had a marked increase in mesenteric lymph node (MLN) dendritic cells (p < 0.01) despite similar T-cell populations. Further analysis, including histopathology, serum cytokine ELISA, fecal corticosterone, 16s rRNA analysis of the microbiome, and RT-PCR analysis of ileum and spleen are currently underway and will be ready by the end of the year. Conclusions: The marked difference in the MLN dendritic cell (DC) population suggests increased luminal sampling of intestinal bacteria. Determining how the microbiome affects or is affected by the altered DC population is of particular interest to us. Is the DC population altered because of the microbiome or is the DC population altering the microbiome? Our preliminary data has suggested that depressive states are associated with alterations in the microbiome. Again, whether the changes are a cause or an effect of depression is yet to be answered but is our immediate goal. Behavioral studies performed on restrained mice (RS) and control mice (n=8 and n=7 respectively). Age and sex-matched littermate controls were used for all experiments. CD11c+ MHC II+ dendritic cell populations were elevated in the restrained (RS) group. Further immunological analysis is currently underway.